Considerations on proper nutrition during pregnancy - Pacheco Romero, José (2014)
Pregestational maternal weight, body mass index and weight gain during pregnancy are factors that influence the newborn’s weight and his weight and health at long term. The following symposium on Nutrition during pregnancy and lactation may guide the health professional to counsel pregnant women and their families on appropriate nutrition for her and her children.